2018
DOI: 10.1186/s13104-018-3349-y
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of severe hospitalized cases of laboratory-confirmed influenza during five epidemic seasons (2010–2015)

Abstract: ObjectiveThe Plan of Information on Acute Respiratory Infections in Catalonia (PIDIRAC) included the surveillance of severe hospitalized cases of laboratory-confirmed influenza (SHCLCI) in 2009. The objective of this study was to determine the clinical, epidemiological and virological features of SHCLCI recorded in 12 sentinel hospitals during five influenza seasons.ResultsFrom a sample of SHCLCI recorded during the 5 influenza epidemics seasons from 2010–2011 to 2014–2015, Cases were confirmed by PCR and/or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Moreover, starting antivirals as soon as possible, especially within 48 hours of onset of symptoms, will help reduce disease severity and loss of function. 19…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, starting antivirals as soon as possible, especially within 48 hours of onset of symptoms, will help reduce disease severity and loss of function. 19…”
Section: Discussionmentioning
confidence: 99%
“…Torner et al, 8 in Catalonia, displayed a similar picture among severe hospitalized cases during five post-pandemic seasons (2010-2015), although the authors hypothesized a bias explained by a greater prevalence of influenza A viruses spread in the population during the observed period.…”
Section: Discussionmentioning
confidence: 86%
“…4,5 Elderly population, defined as those aged 65 years and older, and, more specifically, elderly people with underlying conditions, are at increased risk for hospitalization and death, also in industrialized countries. [6][7][8] The best strategy to prevent influenza is vaccination, the effectiveness of which strongly depends on the variability of circulating viruses, representing a major challenge for public health systems worldwide. 9 Therefore, it is of paramount importance a continuous monitoring of genetic and antigenic features of influenza strains.…”
Section: Introductionmentioning
confidence: 99%
“…Yet some subsets of population are at higher risk for more severe disease which may require hospitalization and/or intensive care unit admission due to complications such as pneumonia or acute respiratory distress. It is well known that the elderly (≥65 years of age) have the highest risk of increased morbidity including respiratory failure, and mortality; It is estimated that over 60% of all seasonal-influenza-related hospitalizations and 90% of seasonal-influenza-related deaths each year occur in the elderly [2,[3][4][5][6][7] in Europe [9], suggest that vaccination offered only slight protection for severe outcome due to this fact and because there was a high proportion of elderly hospitalizations (79.1%) and that older age is associated with a lower ICU admission [10].Data on the inverse relation between age and ICU admission has also been pointed out by other authors who found higher rate of ICU admission among SHCIC at 15-64 y [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1. Laboratory confirmation was carried out by Polymerase Chain reaction (PCR) and/or culture techniques on nasal aspirate or nasopharyngeal swab sampling described in previous publications [4,6,7]. All hospitalized cases were followed up until discharge to determine the disease progression and outcome.…”
Section: Methodsmentioning
confidence: 99%